Case Report: Congenital Drusen of the Retina and Hypertrophy of the Retinal Pigment Epithelium in the Same Eye - Williams, T.D (Canadian Journal of Optometry, 2021)
The patient is a 24 year old caucasian female with no history of ocular or systemic disease and normal visual acuity in each eye. The right eye was urtremarkable, both centrally and peripherally. In the left foveal region a number (roughly a dozen) of orange-colored, discrete circular spots were seen in the deep retina.